To solve the equation \( x^2 - 6x - 16 = 0 \) using the quadratic formula, we start by identifying the coefficients \( a \), \( b \), and \( c \):
- \( a = 1 \)
- \( b = -6 \)
- \( c = -16 \)
The quadratic formula is given by:
\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \]
Now, plug in the values of \( a \), \( b \), and \( c \):
- Calculate the discriminant:
\[ b^2 - 4ac = (-6)^2 - 4(1)(-16) = 36 + 64 = 100 \]
- Substitute into the quadratic formula:
\[ x = \frac{-(-6) \pm \sqrt{100}}{2(1)} = \frac{6 \pm 10}{2} \]
- Solve for the two possible values of \( x \):
- For the positive case:
\[ x = \frac{6 + 10}{2} = \frac{16}{2} = 8 \]
- For the negative case:
\[ x = \frac{6 - 10}{2} = \frac{-4}{2} = -2 \]
Thus, the solutions are:
\[ x = 8 \quad \text{and} \quad x = -2 \]
The correct response is:
x=8, x=−2 (or x equals 8, x equals negative 2)